2012
DOI: 10.1371/journal.pone.0030446
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Target DNA Sequences of DNA-Binding Proteins Based on Unbound Structures

Abstract: DNA-binding proteins such as transcription factors use DNA-binding domains (DBDs) to bind to specific sequences in the genome to initiate many important biological functions. Accurate prediction of such target sequences, often represented by position weight matrices (PWMs), is an important step to understand many biological processes. Recent studies have shown that knowledge-based potential functions can be applied on protein-DNA co-crystallized structures to generate PWMs that are considerably consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…However, methods utilizing 3D structures of TFs do not have these limitations. With an increasing number of solved structures of protein/DNA complexes in Protein Data Bank (PDB) [9], it is becoming more common to identify TFBSs using structural information of solved protein/DNA complexes [10]–[29].…”
Section: Introductionmentioning
confidence: 99%
“…However, methods utilizing 3D structures of TFs do not have these limitations. With an increasing number of solved structures of protein/DNA complexes in Protein Data Bank (PDB) [9], it is becoming more common to identify TFBSs using structural information of solved protein/DNA complexes [10]–[29].…”
Section: Introductionmentioning
confidence: 99%
“…4042 Recent advances in array and sequencing technologies allow genome-wide studies of chromatin modifications. In particular, histones and their post translational modifications serve as key epigenetic marks that are extensively mapped on genomic scale due to their role in gene expression and in chromatin packaging.…”
Section: Epigenomic Bulk Studiesmentioning
confidence: 99%
“…However, (16) also showed that performance may degrade in unbound queries if conformational changes occur upon DNA binding. Therefore, users are encouraged to compare predictions using different templates for figuring out the positions in the predicted PWMs with high confidence.…”
Section: Evaluation and Case Studiesmentioning
confidence: 99%
“…This query protein was selected from the seven testing proteins used in (16) by the following procedures. We queried the seven protein names in the AH-DB (26), a database of protein structure pairs before and after binding, and the query structure (1G6N) turned out to be the unbound structure with the largest root-mean-square deviation (RMSD) of 4.54 to the bound structure upon DNA binding.…”
Section: Evaluation and Case Studiesmentioning
confidence: 99%